Statistical Analysis of Wind Turbine’s Output Power - Nemes, C.; Istrate, M. (Elektronika ir Elektrotechnika, 2012)
In this paper, the authors develop the analytical models for the mean and variance of the output power based on the power curve of wind turbine and the Weibull distribution of wind speed at an investigated site. In order to validate the model, the results are compared with those given by Monte Carlo simulation technique. The analytical models have the advantage to put into the evidence the effects of the wind profile and of the wind turbines’ operational parameter on the values of the statistical moments. The models can be used in the preliminary planning of the electrical power system with new energy wind sources, to evaluate the amount of energy and the variability of the generated electrical power. Ill. 2, bibl. 6, tabl. 2 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.120.4.1447